Integrating Web 2.0 Tools in Writing Class to Promote Assessment for Learning: Mengintegrasikan Alat Web 2.0 di Kelas Menulis untuk Mempromosikan Penilaian untuk Pembelajaran - Rahmawanti, Movi Riana; Umam, Amalul (Universitas Muhammadiyah Sidoarjo, 2019)
Technology has been implemented for instruction with various resources to explore course content and assess students’ learning. In this study, Web 2.0 tools was implemented in writing classroom for Higher education students. A Web 2.0 tools that was used was because it is known as an online means and has been used to perpetuate interactions and communication within a collaborative learning. Assessment is central to teaching and learning, from which a decision whether or not the goals of education are being met. At the same time, the demand of today’s era makes it quite challenging for educators to find the best way to assess their students. Action research method was employed in the study in which observation and individual semi-structured interviews we re used to collect the data. The result of the study is the knowledge of implementation of Web 2.0 tools in EFL (English as foreign language) classroom, from which a guidance of using Web 2.0 tools to promote assessment for learning will be arrived at. This study concludes that Web 2.0 tools can be applied to promote Assessment for learning, and it has several benefits to the student s to improve their learning quality.